“PENGARUH SELF-EFFICACY DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI” (Studi Kasus Pada Kantor Akuntan Publik di Kota Semarang) - Niken Ajeng Pertiwi, 14.05.52.0142; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of self-efficacy, obedience pressure and task complexity on audit judgment. In this study also tested the effect of moderation of task complexity on audit judgment. The population in this study was the auditors who work on a public accouunting firm in the city of Semarang. Sample selection method used was convenience sampling with a total of 101 questionnaires that can be processed. The data analysis technique used is test the value of the absolute difference. Based on the results of tests performed can be seen that the self-efficacy and obedience pressure positive effect, task complexity negative effect on audit judgment. The complexity of the task weakens the effect of self-efficacyand reinforces the effect of obedience pressure on audit judgment made.Keyword: self-efficacy,obedience pressure, task complexity and audit judgment